TRANSFORMING ARCHIVE MANAGEMENT TOWARDS DIGITALIZATION THROUGH THE LOGIC EVALUATION MODEL AT KALIANDA CLASS III IMMIGRATION OFFICE - Wijaya, Tegar Yudha; Mastur, Anida Sri Rahayu; Wirdhiningsih, Virra (Journal of Administration and International Development, 2024)
Abstract. This research focuses on evaluating the management of substantive archives at the Immigration Office Class III Non-TPI Kalianda using the Logic Evaluation Model with the main objective of improving the quality of archival governance. Effective archive management is essential for every institution as archives serve as a primary source of information that supports various administrative activities and decision-making processes. However, at the Immigration Office Class III Non-TPI Kalianda, there are several challenges in archive management, such as a lack of archival facilities, limited human resources, and the absence of a digital archiving system. The identified problems are how the implementation of archive management and the evaluation of substantive archive management using the Logic Evaluation Model can improve the quality of archival governance at the office. This study aims to analyze both aspects. The method used in this research is descriptive qualitative, with data collected through observation, interviews, and documentation. The research results indicate that archive management is not yet optimal, particularly due to a lack of infrastructure and competent human resources. The Logic Evaluation Model was used to evaluate the inputs, activities, outputs, and outcomes of the archiving system. The results show that significant improvements are needed in various aspects to enhance the quality of archival governance. This research provides theoretical benefits in the development of archival management knowledge and practical benefits for the Immigration Office Class III Non-TPI Kalianda to improve the quality of archive management. In conclusion, digital archiving and the enhancement of human resource competencies are essential, and the author suggests the development of archival facilities and training for archive managers as steps for future improvement.